Le Rôle de la Ponctuation, dans la Compréhension d’un Message Ecrit en Français chez les Etudiants LMD: Cas de la Première et Troisième Années-Licence Français - Université de Batna 2 - Azzouzi, Tarek (جامعة الجيلالي ليابس سيدي بلعباس - مخبر البحوث والدراسات الاستشراقية فى حضارة المغرب الإٍسلامى, 2018)
عادة ما تكون علامات ترقيم اللغة الفرنسية عبارة عن حقل يدرس القليل، على الرغم من وجود عدد من البحوث في هذا المجال لمدة عقد من الزمان. عموما "متسمة" بواسطة ممارسات التحرير "العلمية"، أنها مع ذلك معطية أي حقيقة لغوية مهمة: أنها تكشف الهياكل التي تم تشكيل النص من أجلها (موضوع الكتابة) وتعطي القارئ توجها في تفسير الرسالة المكتوبة. لا يمكن لأحد أن يهمل الدور الذي يمكن أن تلعبه علامات الترقيم في تعلم اللغات الأجنبية. أنها وسيلة للترتيب المنهجي وتنظيم اللغة، ولذلك تلعب دورا أساسيا في فهم الرسالة المكتوبة وفكها. ويمكنا أيضا إنشاء معان جديدة أخرى للقارئ وبشكل أكثر تحديدا للطالب الذي يطمح إلى تعيين المعنى الصحيح للوثائق التي يقرأها وخاصة الكتابات التي يكتبها. لذلك لا تزال علامات الترقيم هي أكثر الوسائل التي يمكن لاعتماد عليها للحفاظ على القيمة والمعنى المقصود للوثائق. نظام علامات الترقيم هو عملية معقدة للغاية، تسمح لكل واحد منا بالإشارة إلى الحدود بين مختلف مكونات الجملة المعقدة، لتدوين الترجمات المختلفة والإشارة إلى التنسيقات أو التفرعات بين المقترحات. هذا يسمح لنا أن نقول في النهاية أن علامات الترقيم هي علم متقن للغاية، والذي يشمل علامات مختلفة طبقا لأسلوب الطباعة، التنغيم، والوظيفة وأنها ابعد ما تكون عن كونها فرع ملحق محيط اللسانيات. لقد أتاح العمل الذي سنقدمه فهم مسار علامات الترقيم عبر التاريخ والقواعد التي تحكم نظامه وحالته على مستوى اللغة والأشكال المختلفة التي يمكن أن يتخذها. ومع ذلك يمكن لأي بحث أن يكون مربحا فقط إلى الحد الذي يساعد في إيجاد حلول المشاكل التي تطرحها طبيعة القضايا المثارة. هذا هو سبب تحليلنا في هذا البحث من خلال سلسلة من المقترحات التي يمكن استخدامها لملء الثغرات التي تم تحديدها من خلال تحليل لاختبارات المقدمة للطلاب، دون إهمال تسليط الضوء على الأسباب الحقيقية (لغوية أو خارجها) بعد أن كانت في أصل هذه الصعوبات، لاقتراح حلول مؤقتة لهذه الظاهرة العالمية.
The punctuation of French remains generally an area little studied, despite a number of research conducted in the field for a period of thirty years. Generally, « masked» by « scientific » editing practices, it is nevertheless a significant linguistic fact: it reveals the structures whose text was constituted for the « speaking subject » and gives the reader orientation in the interpretation of the writing message. No one can neglect the role that punctuation can play in learning foreign languages. it is a means of systematization and organization of the language, it plays a key role in understanding and decrypting the writing message. it can also have other new meanings and open other latent or discrete perspectives for the rider and more, especially for a student who aspires to attribute the correct meaning to documents he reads and in particular to the writings he writes. therefore, punctuation is undoubtedly the most reliable way in preserving the value and the intended meaning of the documents. The system of punctuation marks is a very complex process that allows each of us to indicate the boundaries between the various constituents of the complex sentence, to transcribe the various intonations and to indicate the coordination’s or subordinations between the propositions. what allows us to say in the end, that punctuation is a very elaborate science, which encompasses different signs that are classified according to typography, intonation and function and that it is far from being a simple branch attached on the periphery of linguistics. The work we are going to present has made it possible to understand the punctuation journey through history, the rules that govern its system, its status at the level of the language and the different forms it can take. However, any research can be lucrative only to the extent that it helps to find solutions to the problems posed by the nature of the issues raised. this is why our analysis in this research is elaborated by series of proposals that may serve to fill the gaps identified through the analysis of tests offered to students, without neglecting to highlight the real causes (linguistic or extra linguistics) having been at the origin of these difficulties, to finally propose provisional solutions to this universal phenomenon.
Keywords: طلبة الجامعة -- اللغة الفرنسية -- علامات الترقيم -- القواعد اللغوية -- جامعة باتنة 2